Nuclear expression of XBP1s is correlated with breast cancer survival: a retrospective analysis based on tissue microarray - Wang M (OncoTargets and Therapy, 2017)
Mengyi Wang, Shengnan Ruan, Jie Ming, Fang Dong Department of Breast and Thyroid Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China Abstract: An alternatively spliced transcription factor that participates in the unfolded protein response, XBP1 is a novel protein involved in cancer progression and outcome. This study aimed to investigate the relationship of spliced XBP1 (XBP1s) with the clinicopathological characteristics and prognosis of breast cancer by using tissue-microarray analysis. A consecutive series of 170 patients with breast cancer diagnosed between 2001 and 2004 in hospitals in eastern and southern China were included. Immunohistochemical staining for XBP1s was performed, and the expression of XBP1s was separately examined in nuclei and cytoplasm. We found that a higher expression of XBP1s in nuclei strongly correlated with poorer survival (46.7% versus 75%, P=0.018); however, the expression of XBP1s in the cytoplasm had no relationship with survival. Multivariate Cox regression analysis indicated that the expression of XBP1s was not an independent prognostic factor (RR 2.074, 95% CI 0.909–4.736; P=0.083). None of the other clinicopathological characteristics – age, pathology grade, T stage, N stage, TNM stage, estrogen receptor, progesterone receptor, or HER2 status – was found to be correlated with XBP1s expression in the nuclei. In conclusion, independently of other clinicopathological factors, the nuclear expression of XBP1s is correlated with shorter breast cancer survival; however, whether nuclear XBP1s is an independent prognostic biomarker needs to be confirmed by further studies with larger samples and detailed sample stratification. Keywords: breast cancer, tissue microarray, XBP1s, endoplasmic reticulum stress, biomarker